Generation and Oxidative Reactivity of a Ni(II) Superoxo Complex via Ligand-Based Redox Non-Innocence - McNeece, Andrew J. (J Am Chem Soc, 2020)
Metal ligand cooperativity is a powerful strategy in transition metal chemistry. This type of mechanism for the activation of O(2) is best exemplified by heme centers in biological systems. While aerobic oxidations with Fe and Cu are well precedented, Ni-based oxidations are frequently less common due to less-accessible metal-based redox couples. Some Ni enzymes utilize special ligand environments for tuning the Ni(II)/(III) redox couple such as strongly donating thiolates in Ni superoxide dismutase. A recently characterized example of a Ni-containing protein, however, suggests an alternative strategy for mediating redox chemistry with Ni by utilizing ligand-based reducing equivalents to enable oxygen binding. While this mechanism has little synthetic precedent, we show here that Ni complexes of the redox-active ligand (tBu,Tol)DHP ((tBu,Tol)DHP = 2,5-bis((2-t-butylhydrazono)(p-tolyl)methyl)-pyrrole) activate O(2) to generate a Ni(II) superoxo complex via ligand-based electron transfer. This superoxo complex is competent for stoichiometric oxidation chemistry with alcohols and hydrocarbons. This work demonstrates that coupling ligand-based redox chemistry with functionally redox-inactive Ni centers enables oxidative transformations more commonly mediated by metals such as Fe and Cu.